IMPROVING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXTS THROUGH COGNITIVE STRATEGY AT GRADE VII-2 OF SMPN 1 INDRA PRAJA TEMBILAHAN - Etfita, Fauzul (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2014)
This study aims to determine whether cognitive strategy can improve students' skills in writing descriptive text, and what factors affect the improvement of writing skills. This research is a classroom action research conducted in two cycles. Each cycle consists of four meetings. Each consists of plan, action, observation, and reflection. Participants in this study is as straight as the students of class VII-2 SMPN 1 Indra Praja Tembilahan totaling 22 students. The data of this study were collected through: (1) observation sheet; students, teachers, teaching steps (2) field notes (3) interviews, and (4) writing tests. This study found that the use of cognitive strategy can improve students' skills in writing descriptive text. The findings of this study indicate that there is an increase in the average score of students above the completeness criteria of a minimum of English subjects is 75. The factors that influence the skills of students in writing descriptive text are (a) reading material given to the students, (b) motivation students, and (c) teacher's approach to students. So it can be concluded that the application of cognitive strategy on the teaching of reading descriptive text can give positive results with the increase of students' skills in reading descriptive text.